Comparing The Effects Of Rain Classroom, Wechat And Multimedia Teaching Tool On Autonomous Learning And Cognitive Ability Among Biochemistry Course Undergraduates In China - Huang, Jiahui (2023)
This study aimed to investigate the effects of Artificial Intelligence (AI: Rain Classroom), WeChat platform and multimedia teaching tool and how these three teaching platforms enhance students' autonomous learning and cognitive ability in the Biochemistry course. This study used a sequential explanatory mixed methods design.